How can Car2X-Communication improve road safety: A statistical based selection and discussion of feasible scenarios - Sebastian Röglinger; Christian Facchi (Hochschule Ingolstadt - University of Applied Sciences, 2009)
A lot of applications have been sketched in the area of Car2X-Communication. Safety aspects are often mentioned among others as a motivation for Car2X-Communication systems. We present a statistical based selection of feasible applications with the goal of increasing safety. Therefore the official statistical information of the year 2007 has been considered. Additionally we will present some consequences for the introduction of Car2XCommunication systems including infrastructure.
urn:nbn:de:bvb:573-309
Keywords: 650